Energy-efficient Carbon-doped TiO2 for Visible Light Degradation of Methyl Orange: Preparation, Performance, and Mechanism - Han, Xinying; Guo, Yubei; Goh, Chien Yong; Ngan, Cheng Loong; Tan, Jian Ping; Tan, Peng Chee; Lai, Sin Yuan (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
Water pollution caused by textile dyes has become a serious issue, making the treatment of sewage urgent. Carbon-doped TiO2 (C-doped TiO2), using alkanes and polyols as carbon sources, has been found to be light-responsive in degrading dyes. However, there is a lack of studies on the interfacial interaction between carboxylic acids and TiO2. Therefore, citric acid, a triprotic, hexadentate carboxylic acid, was used to dope TiO2 through solvothermal-calcination. The effects of carbon content and calcination temperature on the photodegradation performance of C-doped TiO2 were investigated. The band gap energy of C-doped TiO2 was found to be narrower (2.67 eV) than that of undoped TiO2 (2.88 eV). After carbon doping, the absorption band extended from the UV to the visible regions, lowering the energy required for electron excitation. The functional groups present on C-doped TiO2 assisted in the adsorption of methyl orange (MO), assisting in photodegradation. Only the anatase phase of TiO2 was observed at calcination temperatures between 250 and 400 °C. Photoluminescence analysis revealed that a lower carbon content and slightly higher calcination temperature resulted in better interfacial charge separation and transfer efficiency. The 10 wt% C-doped TiO2 calcined at 300 °C demonstrated the best MO photodegradation efficiency of 62.1% under visible light illumination. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).